APOE‐e4 alters the microglial phenotype in the presence of Alzheimer's disease pathology compared to APOE‐e3. (December 2021) - Kloske, Courtney M; Weekman, Erica M; Xie, Kevin; Patel, Ela; Anderson, Sonya; Bachstetter, Adam D; Morganti, Josh M.; Fardo, David W.; Nelson, Peter T; Wilcock, Donna M
Abstract: Background: APOE is the largest genetic risk factor for late‐onset Alzheimer's disease (AD) with the APOE‐e4 allele conferring an increased risk for AD compared to the APOE‐ e3 allele. While APOE in the brain is a lipid transporter produced by astrocytes, research has shown that APOE can impact diverse biochemical pathways. Interestingly, APOE isoforms have also been shown to modulate levels of neuroinflammation in the brain, yet the exact impact on inflammation remains unknown. As microglia are considered to be a primary source of brain inflammation, this study explores how APOE isoforms impact microglial morphology and activation state in human brains. Method: Two methods were used in this study to assess the impact of APOE isoforms on microglia in human brain sections. First, NanoString Digital Spatial Profiling (DSP) was used to investigate protein levels of inflammatory markers specific for microglia on fixed tissue in the hippocampus with AD pathology in both APOE‐ e3 (n=7) and APOE‐ e4 (n=8) subjects. Immunohistochemistry (IHC) was then performed using samples from APOE‐ e3/3 (n=33 control n=23 AD), APOE‐ e4/4 (n=19 AD), and APOE‐e3/4 (n=15 control) subjects from the University of Kentucky AD Research Center. IBA‐1 IHC was used to investigate microglial activation and morphology differences between APOE isoforms. Result: Using both DSP and IHC, the results indicate that APOE isoforms play a role in the microglial changes seen in the presence of AD pathology‐ both in activation state and morphology. The DSP experiments showed significant changes in microglial markers throughout the hippocampal region between APOE‐ e3 and APOE‐ e4. Of interest, in APOE‐e3 subjects, we show an alteration of the microglial phenotype based on pathology level, however, in APOE‐e4 subjects, this change due to pathology is reduced. Additionally, in the IHC experiments we found changes in microglial morphology and activation that parallel those seen in DSP. Conclusion: The findings from this study suggest that with APOE‐ e3, microglia are able to respond in the presence of AD pathology. By contrast, APOE‐ e4 microglia cannot produce an appropriate response to AD pathology. Overall, these findings help highlight the role of the APOE isoforms in AD and neuroinflammation.